Effects of mulberry extract on the liver pathology and serum biochemical parameters in carmustine administrated rats - Ipek, Volkan; Balkan, Burcu Menekse; Inanc, Muhammed Enes; Kaplan, Oguzhan; Corum, Orhan; Gungor, Sukru; Karaca, Harun; Ata, Ayhan (SAGE Publications, 2021)
BACKGROUND: Carmustine is a chemotherapeutic agent that is mainly used in the treatment of glioblastoma and can cause toxic effects on various organs, including the liver. The white mulberry extract has anti-apoptotic and anti-oxidant effects. OBJECTIVE: The study aimed at investigating the effects of the dried white mulberry extract on the pathology, apoptosis, and oxidative stress in the liver, as well as the levels of serum adenosine deaminase, glutathione peroxidase, superoxide dismutase, ceruloplasmin, paraoxonase, and malondialdehyde in carmustine-administrated rats. METHODS: Forty-two rats divided into six groups were used in this study. BCNU was administrated intraperitoneally (IP) (5 mg/kg body weight (BW)/week) for 10 weeks to the BCNU and BCNU-DWME groups. DWME was administered (600 mg/kg-BW by oral gavage) daily for 10 weeks to the DWME and BCNU-DWME groups. After the experimental procedure, histopathological, immunohistochemical, and biochemical analyses were performed. RESULTS: Carmustine caused biliary hyperplasia at a dose of 5 mg/kg. However, the mulberry extract was not effective in alleviating this pathology. Furthermore, the administration of carmustine induced apoptosis in hepatocytes, and the mulberry extract had an anti-apoptotic effect. Carmustine increased the 8-OHdG activity in the liver, and dried mulberry extract ameliorated this activity. Although there was no significant difference in the serum oxidative stress parameters between the groups, carmustine significantly increased the adenosine deaminase activity during the recovery period, while mulberry extracts partially ameliorated these effects in the recovery period. CONCLUSIONS: Dried white mulberry extract has anti-apoptotic and anti-oxidative effects against carmustine-induced toxicity.
Keywords: 3. Good health